1986
DOI: 10.1080/00420988620080761
|View full text |Cite
|
Sign up to set email alerts
|

Residential Location and Intra-urban Mobility in a Developing Country: Some Empirical Observations from Benin City, Nigeria

Abstract: While rural-urban migration has been a major focus of studies in developing economies intra-city mobility has received very little attention. This article examines the locational pattern, and subsequent residential mobility, of new migrants in Benin City, Nigeria. The study shows that as a result of sentimental attachment to village of origin migrants from the adjoining rural region tend to have a bias in their city location for a sector of the city lying in the same direction with their village of origin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 5 publications
(11 reference statements)
1
14
0
1
Order By: Relevance
“…For example, in China households seeking for a home are willing to pay more for reputable sectors and for areas where the quality of neighbourhood with respect to security, accessibility and convenience is high (Wang & Li, 2006). In line with this Ozo (1986) observed that new migrants in Benin City settled in the outer zone because the central city was saturated and some also are attracted to the outskirts because of the possibility of engaging in informal activities that required space e.g. car repair workshops and the opportunities for unskilled work such as causal labourers.…”
Section: Neighbourhood and Environmental Attractivenessmentioning
confidence: 56%
See 4 more Smart Citations
“…For example, in China households seeking for a home are willing to pay more for reputable sectors and for areas where the quality of neighbourhood with respect to security, accessibility and convenience is high (Wang & Li, 2006). In line with this Ozo (1986) observed that new migrants in Benin City settled in the outer zone because the central city was saturated and some also are attracted to the outskirts because of the possibility of engaging in informal activities that required space e.g. car repair workshops and the opportunities for unskilled work such as causal labourers.…”
Section: Neighbourhood and Environmental Attractivenessmentioning
confidence: 56%
“…The decision of households to reside in a particular sector within a city could be due to socioeconomic status (de Palma et al, 2007;Zondag & Pieters, 2005;Weisbrod et al, 1980), administrative and central character (Andrew & Meen, 2006;Axhausen et al, 2004;, Sociocultural network and ethnic ties (Ozo, 1986;Owusu, 2004;Kapoor et al, 2004), environmental and neighbourhood attributes (Clarke et al, 2006;Galster & Santiago, 2006), etc. Urban residential location models (Alonso, 1964;Muth, 1969;Mills, 1967Mills, , 1972 indicate that the determinants of choice of residential location include income of the household, family size, population density, rent and cost of movement.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations